Magnetite water based ferrofluid flow and convection heat transfer on a vertical flat plate: Mathematical and statistical modelling - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Mohd Zuki, Salleh (Elsevier Ltd., 2022)
The unique magnetic properties of ferrofluid when exposed to the magnetic field led to the ferrofluid formulation in wide applications, especially as a thermal transfer. To picture the effective ferrofluid flow configurations and heat transfer mechanism at a surface, it is crucial to figure out the phenomenology of boundary layer and convective heat transfer. This study investigates a numerical solution of the mixed convection boundary layer flow of ferrofluid at the stagnation point on a vertical flat plate. Ferrofluid composed of magnetite (Fe3O4) water based exposure to the magnetic field and thermal radiation is considered. The complicated governing differential equations of fluid flow and heat transfer are simplified into simple equations using boundary layer approximation, Boussinesq approximation and similarity transformations. Then, the equations are solved numerically by employing the Keller-box method. Numerical results discovered that the ferroparticles volume fraction is the predominant factor in contributing to the trend of ferrofluid velocity, reduced skin friction and reduced Nusselt number. Further, the influence of the ferroparticles volume fraction on reduced skin friction and reduced Nusselt number are analyzed using regression analysis.